Comparing the Determinants of Worldwide Homicide and Terrorism - LaFree, Gary (Journal of contemporary criminal justice, 2024)
Over the past two decades, the study of terrorism has been increasingly integrated into mainstream criminology. Like other types of criminal behavior, terrorism can be divided into etiology (an emphasis on “breaking laws”) and criminal justice (an emphasis on “making laws” and “reacting toward the breaking of laws”). Moreover, like the study of crime, the study of terrorism is inherently multidisciplinary. Nevertheless, terrorism differs from more common forms of crime in fundamental ways: Terrorist perpetrators, unlike common criminals, rarely see themselves as criminal, often seek rather than eschew publicity, and often have broader political goals. Despite similarities and differences, we could identify little prior research that has directly compared the determinants of terrorism and more ordinary types of crime. In this article, we create large cross-national datasets on homicides and terrorist attacks and then compare the effects of a set of common economic, political, and social variables on each. We find a good deal of similarity in the determinants of the two types of violence. Both homicide and terrorism are more common in countries with high GDP, high percent urban, high ethnic fractionalization, and in countries moving toward democratization. Both homicide and terrorism are low in countries experiencing high globalization. Although homicides are more common in countries experiencing high levels of inequality and poverty, neither of these two variables is significantly associated with terrorist attacks. We discuss the implications of the findings for theory, policy, and future research.